Jurisdiction in employment matters under Brussels I: a reassessment - Grušic, Uglješa (Cambridge University Press, 2012)
This article examines the rules of jurisdiction in employment matters of Brussels I. It focuses on a paradox in that these rules aim to protect employees jurisdictionally, but in fact fail to accord employees a more favourable treatment when they need it most, namely when they appear as claimants. The article argues that the current rules fail to achieve the objective of employee protection, examines the reasons for this, proposes certain amendments that would improve the existing rules, and thereby engages in the debate surrounding the forthcoming review of Brussels I.The author was awarded the 2012 ICLQ Young Scholar Prize for this article.